Foliar application of zinc selenide enhances drought tolerance in maize - Djanaguiraman, M; Kanna, V K (Plant Science Today, 2025)
Drought stress severely limits maize (Zea mays L.) growth and grain yield. Foliar application of nanomaterials with antioxidant properties offers a promising strategy for mitigating drought effects. This study evaluated the potential of zinc-selenide quantum dots (ZnSe QDs) to improve drought tolerance in maize. A pot experiment was conducted using a factorial randomised block design (RBD). The first factor was the irrigation regime with 2 levels: (i) irrigated control, where plants were watered daily to maintain 0.9 fraction of transpirable water (FTSW) and (ii) drought-stressed, where plants experienced progressive soil drying from 0.95 to 0.05 FTSW. The second factor was foliar spray with 3 levels: (i) water spray, (ii) combined zinc sulphate (10 mg L-1) and sodium selenate (10 mg L-1) spray (Zn+Se) and (iii) ZnSe QDs (20 mg L-1). The field trial used the same treatment structure. Under drought conditions, foliar application of ZnSe QDs at 20 mg L-1 during the vegetative stage significantly (p<0.05) increased photosystem II quantum yield by 10 %, leaf water content by 22 % and stomatal conductance by 28 % compared to water spray. The rise in photosynthetic rate (28 %) under drought was linked to increased tissue water content, catalase activity (47 %) and peroxidase activity (60 %). During the reproductive stage, ZnSe QDs spray enhanced the number of seeds m-² and individual seed weight, leading to increased seed yield under drought stress. These findings demonstrate that foliar application of ZnSe QDs at 20 mg L-1 can mitigate drought-induced effects in maize.